THE SIGNIFICANCE OF ELECTRONIC EDUCATIONAL-METHODICAL RESOURCES IN THE FORMATION OF HISTORICAL THINKING (Multidisciplinary Journal of Science and Technology, 2025)
The article analyzes the role of electronic educational-methodical resources such as electronic textbooks, virtual museums, interactive maps, multimedia platforms, and gamification in the development of historical thinking. It argues that through such resources, students develop skills in deeply comprehending historical events, analyzing sources, and drawing independent conclusions. In particular, the opportunities offered by platforms such as Smithsonian Learning Lab, Europeana, ZiyoNET, and EduMarket are demonstrated to enhance the quality of education, motivation, and analytical thinking, both scientifically and practically.